PENGARUH EKSTRAK Tagetes erecta L TERHADAP PERTUMBUHAN JAMUR Saprolegnia sp SECARA IN VITRO - Sufal Diansyah; Farah Diana (JURNAL PERIKANAN TROPIS, 2017)
Saprolegnia sp fungi are freshwater mushrooms that live in freshwater environments and require water to grow and reproduce. Mushroom Saprolegnia is a major type of water fungus that is associated with fungal infections of fish and eggs that are in freshwater. Saprolegnia sp fungus is also called a cold water fungus because it spreads in cold water. Saprolegnia fungus growth in fish / egg bodies or suitable substrate is affected by water temperature. Saprolegnia sp attack causes clinical symptoms that are filled with white threads such as cotton grown in fish eggs. To overcome this problem needed a solution for the prevention of fungal infections one of them is by using anti-fungal herbs such as chicken shoot leaves (Tagetes erecta L). therefore this research needs to be done to control fungal infections Saprolegnia sp on tawes fish eggs. This study used a complete randomized design (RAL), each treatment was repeated three times, the treatment was: P0 = ppm, P1 = 400 ppm, P2 = 600 ppm, and P3 = 800 ppm. The results showed that the most effective extraction was found in treatment P1 with an average value of 14%.